Software engneering - Aggarwal, K. K.; Singh, Yogesh (Delhi: New Age International Publishers, 2024)
This book is designed as a textbook for the first course in software engineering for undergraduate and postgraduate students. This may also help the software professionals to implement software engineering concepts and practices. The suggestions of students, teachers, researchers and practitioners have found a place in this edition. The book has theory from its very beginning. The foundations have been laid very carefully and the treatment is rigorous based on modern lines. In this edition Glossary of Software Engineering has been included at the end of the book. It will help the students in their study and understanding the subject in a better way. Updates in the text have been made wherever necessary.
Includes answers, index and glossary
Keywords: Software engineering -- Computer software$1 (BDevelopments -- Computer programming -- System analysis -- Project management